1989
DOI: 10.1111/j.1600-0722.1989.tb01446.x
|View full text |Cite
|
Sign up to set email alerts
|

Salivary immunoglobulins, lysozyme, pH, and microbial counts in children receiving anti‐neoplastic therapy

Abstract: – Salivary immunoglobulins, lysozyme, pH, and microbial counts were determined in 55 children with cancer diseases (37 cured subjects and 18 acute ones) and 103 healthy subjects. 5–10 ml unstimulated whole saliva was collected and pH, immunoglobulins and lysozyme were measured. Chairside dip‐slide cultivations were used for microbiologic cultures. Reduced salivary pH and an increased amount of lysozyme were found in the saliva of those children who had been cured of their cancer diseases, but ongoing cancer d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…[20][21][22] This study shows that S. mutans counts of the study group were significantly higher than the normal population. This result is supporting the reported results of Pajari et al [23] They claimed that S. mutans amount increases in cancer suffered patients and cured patients. Furthermore, conflicting results have been reported by Ou-Yang et al, [12] O'Sullivan et al [8] O'Sullivan et al [8] showed that the S. mutans level is lower during chemotherapy versus pre-treatment or post-treatment levels; Ou-Yang et al [12] mentioned that S. mutans level in children suffering ALL is lower than normal group, they were against our results.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…[20][21][22] This study shows that S. mutans counts of the study group were significantly higher than the normal population. This result is supporting the reported results of Pajari et al [23] They claimed that S. mutans amount increases in cancer suffered patients and cured patients. Furthermore, conflicting results have been reported by Ou-Yang et al, [12] O'Sullivan et al [8] O'Sullivan et al [8] showed that the S. mutans level is lower during chemotherapy versus pre-treatment or post-treatment levels; Ou-Yang et al [12] mentioned that S. mutans level in children suffering ALL is lower than normal group, they were against our results.…”
Section: Discussionsupporting
confidence: 83%
“…Based on the Sepet et al [36] studies, pH was in normal interval in ALL children, whereas in Pajari et al [23] and Hegde et al [37] studies, pH depletion was observed among ALL children. This similarity can be due to the time of oral examination; examinations of both groups were done before noon that was at least 1 h after their last meal, that is a sufficient time interval for adjusting pH by saliva.…”
Section: Discussionmentioning
confidence: 99%
“…[49][50][51][52] However, chemotherapy appears to cause less acute damage alone than in combination with cranial irradiation or total body irradiation. 16,53,54 It has also been suggested that the administration of anticholinergic anti-emetics during early phases of chemotherapy may also reduce salivary flow. 48 Autopsies on adult recipients of doxorubicin and cyclophosphamide showed histopathologic changes, such as ductal dilatation, cyst formation, acinar degeneration, and infiltration in inflammatory cells in salivary gland tissue, 48 which may, at least partly, explain the findings observed in our participants.…”
Section: Discussionmentioning
confidence: 99%
“…colonies in the saliva of children during anticancer therapy than in the healthy controls. Pajari et al observed that in children undergoing intensive chemotherapy, non-stimulated saliva contained increased number of Streptococcus mutans and Lactobacillus spp., elevated activity of lysozyme and decreased pH of the saliva [19]. Krzemiński and Majda-Stanisławska investigated the prevalence and the number of cariogenic bacteria in children with acute lymphoblastic leukemia undergoing intensive chemotherapy and in healthy children.…”
Section: Discussionmentioning
confidence: 99%